Chiral Helimagnetism and One‐Dimensional Magnetic Solitons in a Cr‐Intercalated Transition Metal Dichalcogenide. Issue 35 (24th July 2021) - Zhang, Chenhui; Zhang, Junwei; Liu, Chen; Zhang, Senfu; Yuan, Ye; Li, Peng; Wen, Yan; Jiang, Ze; Zhou, Bojian; Lei, Yongjiu; Zheng, Dongxing; Song, Chengkun; et al.
Abstract: Chiral magnets endowed with topological spin textures are expected to have promising applications in next‐generation magnetic memories. In contrast to the well‐studied 2D or 3D magnetic skyrmions, the authors report the discovery of 1D nontrivial magnetic solitons in a transition metal dichalcogenide 2 H ‐TaS2 via precise intercalation of Cr elements. In the synthetic Cr1/3 TaS2 (CTS) single crystal, the coupling of the strong spin–orbit interaction from TaS2 and the chiral arrangement of the magnetic Cr ions evoke a robust Dzyaloshinskii–Moriya interaction. A magnetic helix having a short spatial period of ≈ 25 nm is observed in CTS via Lorentz transmission electron microscopy. In a magnetic field perpendicular to the helical axis, the helical spin structure transforms into a chiral soliton lattice (CSL) with the spin structure evolution being consistent with the chiral sine‐Gordon theory, which opens promising perspectives for the application of CSL to fast‐speed nonvolatile magnetic memories. This work introduces a new paradigm to soliton physics and provides an effective strategy for seeking novel 2D magnets. Abstract : Chiral helimagnetism and 1D magnetic solitons are discovered in Cr‐intercalated 2 H ‐TaS2 . The chiral helimagnetic structure has an initial period of ≈25 nm, and it transforms into a chiral soliton lattice in an external magnetic field. The spatial period evolution of this topological spin texture obeys the chiral sine‐Gordon theory, revealing great potential for fast‐speed racetrack memories.